THE EFFECT OF WORK MOTIVATION AND JOB SATISFACTION ON ORGANIZATIONAL COMMITMENT AT PT SUMBER ALFARIA TRIJAYA TBK (ALFAMART) IN SERPONG DISTRICT - Septiani, Helina Dewi; Gani, Nur Asni (UNIVERSITAS PAKUAN, 2025)
This study aims to analyze the effect of work motivation and job satisfaction on organizational commitment at PT Sumber Alfaria Trijaya Tbk (Alfamart) in Serpong District. Organizational commitment is an important factor in determining the success of an organization, including in reducing employee turnover rates. This study uses a quantitative approach with an associative research design. Primary data were collected through questionnaires distributed to 66 Alfamart employees selected using non-probability saturated sampling. The results of the analysis indicate that work motivation has a negative and insignificant effect on organizational commitment, with a calculated t value (1.974) smaller than the t table (1.998) and a significance value of 0.053 greater than 0.05. Conversely, job satisfaction has a positive and significant effect on organizational commitment, with a calculated t value (3.182) greater than the t table (1.998) and a significance value of 0.002 smaller than 0.05. These findings indicate that although work motivation does not have a significant effect on organizational commitment, job satisfaction has a strong positive effect. This study is expected to provide insight for companies to improve organizational commitment through increasing employee job satisfaction